Small-Group Student Talk Before Individual Writing in Tertiary English Writing Classrooms in China: Nature and Insights - Li, Hui Helen; Zhang, Lawrence Jun; Parr, Judy M. (Frontiers in Psychology, 2020)
When exploring the nature of small-group student talk in English-as-a-foreign language (EFL) individual writing in terms of what students are talking about, previous studies have mainly linked it to students’ writing and focused more on students’ written texts than their talk. Consequently, the analyses have largely been text-oriented rather than talk-oriented and have failed to reveal a complete picture of such talk and the socially negotiated nature of the interaction. To fill up the literature gap, we designed a study to investigate the nature of prewriting small-group student talk in Chinese tertiary EFL writing classrooms. Specifically, we examined what students were talking about when engaging in argumentative writing tasks prior to individual writing. Eight hours of audio recordings of student talk from eight small groups in two classes (N=48) were collected during their prewriting small-group discussions. They were analysed and interpreted in six categories: Content talk, language talk, task-management talk, organisation talk, affective talk, and phatic talk. Major findings show that small-group student talk: 1) enabled students to generate content, language, and organization for their proceeding individual writing in small-group student talk; 2) provided them with opportunities to facilitate collaborative linguistic problem-solving and the deliberate use of the first language (L1) for requesting and clarifying information; 3) allowed them to organize the group and scaffold each other collectively to manage the ongoing process of the task; and 4) assisted them to share their emotions and maintain group harmony at a surface level but did not help generate direct positive or negative affective expressions. Pedagogical insights into L2 writing instruction are also discussed.